Practical robust control of cable-driven robots with feedforward compensation. (July 2020) - Wang, Yaoyao; Liu, Lufang; Chen, Jiawang; Ju, Feng; Chen, Bai; Wu, Hongtao
Highlights: Propose a novel robust control with feedforward compensation. Prove the stability of the closed-loop control system considering the proposed dynamics. Demonstrate the validity of proposed method through both simulations and experiments. Abstract: For the trajectory tracking purpose of cable-driven robots, a novel robust control method is proposed and investigated in this paper. The proposed method consists of three elements, i.e. a time-delay estimation (TDE) element and a nonsingular fast terminal sliding mode (NFTSM) control element and a feedforward compensation. The TDE technique is utilized to estimate the lumped system dynamics in a simple but effective way, and then ensures an attractive model-free control scheme. The NFTSM control element is adopted to guarantee precise and robust control performance with continuous and singularity-free control efforts. Moreover, the feedforward compensation is also utilized to further enhance the control performance by taking advantages of the system dynamics. Due to this feedforward compensation element, higher control performance has been ensured compared with the traditional TDE-based control. Thanks to above three elements, the proposed method is practical to use and highly accurate and strongly robust . Comparative simulations and experiments were conducted to verify the effectiveness and superiorities of our proposed control method over the recently proposed one.